Strategi Kepala Sekolah dalam Penanganan Bullying di SMA Islamiyah Bawean - Nasir, Moh.; Aisyah, Sitti (Journal of Education Management Research, 2024)
The Principal's strategy is a plan that a leader wants to achieve at school starting from planning, monitoring, and evaluating to achieve the planned goals. Bullying is an aggressive ready that is carried out either individually or in groups where the perpetrator is stronger, which is done by hurting, oppressing which can cause psychological and physical disturbances to a person. The problems studied are: Principal's Strategy in handling Bullying at Islamiyah Bawean High School. problem formulation as follows: 1) How is the form of bullying in SMA Islamiyah Bawean. 2) What are the factors of bullying at Islamiyah Bawean High School. 3) How is the Principal's Strategy in handling Bullying at Islamiyah Bawean High School? The research method used in this research is qualitative method, while the data collection techniques used are observation, interview, and documentation techniques. The data analysis techniques used are data reduction, data display, and conclusion drawing/ verification. Data checking uses extended observation, source triangulation, technique triangulation, time triangulation. The results in this study are the forms of bullying that occur at SMA Islamiyah Bawean, namely: verbal and physical where the factors for verbal bullying behavior are due to lack of confidence, physical differences. While the factors that cause physical bully behavior are hitting each other so that one of them feels hurt. The principal's strategy in handling bullying at school is one of them: by providing socialization related to the dangers of bullying, good communication between school residents.